EFFECT OF SELF EFFICACY AND MOTIVATION ON THE PERFORMANCE OF POSYANDU CADRES REGARDING EARLY DETECTION OF DEVELOPMENTAL DELAYS IN CHILDREN - ESTER RATNANINGSIH; Listia Dwi Febriati; Aan Ika Sugathot (Jurnal Smart Kebidanan, 2024)
Developmental delay in children is considered a crucial problem in Indonesia. Self-efficacy and motivation are included as internal factors that can influence the performance of Integrated Healthcare Post (Posyandu) cadres regarding early detection of developmental delays in under-five children. High level of motivation and self-efficacy may influence willingness to work hard and achieve high work productivity. Objective of this research to analyze the relationship between self-efficacy and motivation with the performance of Posyandu cadres regarding early detection of developmental delays in under-five children. This was a quantitative observational study with a cross sectional approach. This study was conducted from June to August 2024 which involved 100 cadres in the work area of Banguntapan II Community Health Center. The variables in this study were self-efficacy, motivation and performance. Data were collected using a questionnaire. Data were analysed through univariate and bivariate analysis using the chi square test. 79% of cadres had a high level of self-efficacy, 78% of cadres had a high level of motivation and 76% of cadres had a good performance regarding early detection of developmental delays in children and there was a significant relationship between self-efficacy and motivation with the performance of cadres (p=0.000). Self-efficacy and motivation were closely related to the performance of cadres regarding early detection of developmental delays in children.